2017
DOI: 10.1002/aur.1778
|View full text |Cite
|
Sign up to set email alerts
|

Social skills training for children with autism spectrum disorder using a robotic behavioral intervention system

Abstract: We designed a robot system that assisted in behavioral intervention programs of children with autism spectrum disorder (ASD). The eight-session intervention program was based on the discrete trial teaching protocol and focused on two basic social skills: eye contact and facial emotion recognition. The robotic interactions occurred in four modules: training element query, recognition of human activity, coping-mode selection, and follow-up action. Children with ASD who were between 4 and 7 years old and who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 43 publications
5
97
0
3
Order By: Relevance
“…To date, nearly 30 robots were tested as remedial tools for ASD [e.g., : Labo-1 (Werry et al, 2001); Muu (Miyamoto et al, 2005), Robota (Billard et al, 2007), FACE (Pioggia et al, 2007), Keepon (Kozima et al, 2007), Aibo (Francois et al, 2009), IROMEC (Iacono et al, 2011), Charlie (Boccanfuso and O'Kane, 2011), NAO (Shamsuddin et al, 2012), Flobi (Damm et al, 2013); GIPY-1 (Giannopulu, 2013), Pleo (Kim et al, 2013), KASPAR (Wainer et al, 2014), Darwin-OP (Peng et al, 2014), Pabi (Dickstein-Fischer and Fischer, 2014), Zeno (Salvador et al, 2015), Jibo (Guizzo, 2015), Probo (Simut et al, 2016), Maria (Valadao et al, 2016), Sphero (Golestan et al, 2017), CARO (Yun et al, 2017), KiliRo (Bharatharaj et al, 2018), MINA (Ghorbandaei Pour et al, 2018), QTrobot (Costa et al, 2018), Milo (Chalmers, 2018), Leo (She et al, 2018), Daisy (Pliasa and Fachantidis, 2019), SAM (Lebersfeld et al, 2019), SPRITE (Clabaugh et al, 2019), Actroid-F (Yoshikawa et al, 2019) etc. ].…”
Section: Robots and Asdmentioning
confidence: 99%
“…To date, nearly 30 robots were tested as remedial tools for ASD [e.g., : Labo-1 (Werry et al, 2001); Muu (Miyamoto et al, 2005), Robota (Billard et al, 2007), FACE (Pioggia et al, 2007), Keepon (Kozima et al, 2007), Aibo (Francois et al, 2009), IROMEC (Iacono et al, 2011), Charlie (Boccanfuso and O'Kane, 2011), NAO (Shamsuddin et al, 2012), Flobi (Damm et al, 2013); GIPY-1 (Giannopulu, 2013), Pleo (Kim et al, 2013), KASPAR (Wainer et al, 2014), Darwin-OP (Peng et al, 2014), Pabi (Dickstein-Fischer and Fischer, 2014), Zeno (Salvador et al, 2015), Jibo (Guizzo, 2015), Probo (Simut et al, 2016), Maria (Valadao et al, 2016), Sphero (Golestan et al, 2017), CARO (Yun et al, 2017), KiliRo (Bharatharaj et al, 2018), MINA (Ghorbandaei Pour et al, 2018), QTrobot (Costa et al, 2018), Milo (Chalmers, 2018), Leo (She et al, 2018), Daisy (Pliasa and Fachantidis, 2019), SAM (Lebersfeld et al, 2019), SPRITE (Clabaugh et al, 2019), Actroid-F (Yoshikawa et al, 2019) etc. ].…”
Section: Robots and Asdmentioning
confidence: 99%
“…Ge et al [136] used Kinect to track the engagement level of the participant. Yun et al also used Kinect to track the activity of the participant when he/she is interacting with a social robot [137]. Kinect has also been used to track the movement patterns of the participations [29] and for self-modeling intervention for children with ASD [138].…”
Section: Human Motion Tracking Via Depth Sensorsmentioning
confidence: 99%
“…The results in this study were generally in line with those of previous studies using simple robots in the treatment of ASD. Yun et al . reported that a simple humanoid robot could establish eye contact with individuals with ASD more frequently than a human therapist could.…”
Section: Discussionmentioning
confidence: 99%
“…The results in this study were generally in line with those of previous studies using simple robots in the treatment of ASD. Yun et al 56 reported that a simple humanoid robot could establish eye contact with individuals with ASD more frequently than a human therapist could. Moreover, a previous study argued that a robot that does not show human-like subtle expressions has an advantage in keeping individuals with ASD interested in communication 57 compared to human caregivers.…”
Section: Discussionmentioning
confidence: 99%